Social Work Continuing Education: Current Issues and Future Direction. Issue 4 (7th August 2016) - Kurzman, Paul A.
ABSTRACT: Continuing education is arising as an area of rapid growth and increased attention in the social work profession. Conceptually, the impetus and focus are on the promotion of the principles of lifelong learning and professional replenishment; but pragmatically, the driving force has been the virtually universal requirement of continuing education hours for social work licensure renewal. This article lays out the history of continuing social work education and discusses the current and emerging issues herein for the profession.